Global Perspectives on Financial Policy Optimization: Addressing Overinvestment and its Impact on Corporate Profitability (Study on Indonesia Stock Exchange) - Saputra, Muhammad Haris; R, Mardiana; Fahdillah, Yosi; Yuliana, Yuliana (SENTRALISASI, 2024)
The primary objective of this research is to investigate the impact of overinvestment on corporate performance. It also seeks to analyze the effectiveness of debt policy, dividend policy, and the combined use of debt and dividend policy in alleviating the adverse effects of overinvestment on corporate performance. The study utilizes data from a sample of 53 non-financial companies that carried debt and consistently distributed dividends from 2010 to 2022. Overinvestment is assessed through two methods: the residual value derived from the new investment equation and the Hodrick-Prescott (HP) filter. The data is then transformed into panel data, and various models such as fixed effect, random effect, and common effect are applied to identify the most suitable model. The findings indicate a negative correlation between overinvestment and corporate performance. Debt policy emerges as a mitigating factor, addressing agency conflicts and reducing the adverse impact of overinvestment on company performance. Similarly, dividend policy proves effective in mitigating the negative effects of overinvestment by constraining excess cash. The combination of debt and dividend policies is identified as a comprehensive strategy to mitigate overinvestment, as it aids in curbing excessive free cash flow. However, it is noted that this combination also lowers financing funds to their minimum level, potentially leading to a shortage of funds for future profitable projects. Consequently, careful calculations are emphasized to ensure companies strike a balance, avoiding neglect of profitable investments in the future.